Structural and electrical properties characterization of (1-x)PbZr 0.52Ti0.48O3-xBaFe0.5Nb 0.5O3 system - S. Eitssayeam (2018)
The structural and electrical properties of (1-x)PbZr0.52Ti 0.48O3-xBaFe0.5Nb0.5O3 ceramics system with the composition near the morphotropic phase boundary were investigated as a function of the BaFe0.5Nb0.5O 3 content by X-ray diffraction (XRD) and dielectric measurement technique. Studies were performed on the samples prepared by solid state reaction for x=0.1, 0.2, 0.3, 0.4 and 0.5. The XRD analysis demonstrated that with increasing BFN content in (1-x)PZT-xBFN, the structural change occurred from the tetragonal to the cubic phase at room temperature. Changes in the dielectric behavior were then related to these structural depending on the BFN content.